Evaluation of the Impact of Some Single-Nucleotide Gene Polymorphisms on the Development of Adenomatous Polyps of the Colon in Patients with Irritable Bowel Syndrome - Kyrian, Olena; Dorofeyev, Andrey; Derkach, Igor; Zhigal, Yulia (Turkish Journal of Gastroenterology, 2023)
Background: The number of cases of irritable bowel syndrome is growing worldwide, in which adenomatous polyps can develop as a result of microinflammation of the colonic epithelium. Our study was aimed at the identification of the possible effect of single-nucleotide polymorphisms on the risk of the development of irritable bowel syndrome-related colonic adenomatous polyps. Materials and Methods: The study involved 187 irritable bowel syndrome patients. The single-nucleotide polymorphisms were investigated by the polymerase chain reaction method and DNA was extracted with the phenol-chloroform: interleukin-1β gene-31C/T (rs1143627), -511C/T (rs16944); interleukin-6 gene-174G/C (rs1800795); interleukin-10 gene-592C/A (rs1800872), -819T/C (rs1800871), -1082A/G (rs1800896); Toll-like receptor-2 gene Arg753Gln (rs5743708); Toll-like receptor-4 gene Thr399ile (rs4986791), Asp299Gly (rs4986790); and metalloproteinase-9 gene-8202A/G (rs11697325). The study of polymorphic loci was checked for compliance with the Hardy– Weinberg equilibrium using Fisher’s exact test along with the analyses of the frequency of alleles and the genotypes. Results: The association of diseases with G allele Toll-like receptor-2 gene Arg753Gln (rs5743708) was revealed in irritable bowel syndrome patients with adenomatous polyps of the colon (P < .0006) and AG single-nucleotide polymorphisms s of Toll-like receptor-2 gene (χ2 = 12.78, P < .002); A allele had a protective effect. The AG genotype metalloproteinase-9 gene-8202A/G (rs11697325) polymorphism in irritable bowel syndrome patients with adenomatous polyps of the colon had a protective effect (P < .05). AA genotype interleukin-10 gene-1082A/G (rs1800896) polymorphism in the irritable bowel syndrome patient (χ2 = 33.97, 4.0E-8) can be considered as the risk for adenomatous polyps of the colon in irritable bowel syndrome. Conclusion: G allele Toll-like receptor-2 gene Arg753Gln (rs5743708) and AA genotype interleukin-10 gene-1082A/G (rs1800896) polymorphisms can be the marker of the emergence of adenomatous polyps of the colon concomitant with irritable bowel syndrome. Cite this article as: Kyrian O, Dorofeyev A, Derkach I, Zhigal Y. Evaluation of the impact of some single-nucleotide gene polymorphisms on the development of adenomatous polyps of the colon in patients with irritable bowel syndrome. Turk J Gastroenterol. 2023;34(8):822-830.